2013
DOI: 10.1590/0103-6440201302155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbamide Peroxide Bleaching Gel on Composite Resin Flexural Strength and Microhardness

Abstract: This study investigated the effect of 16% carbamide peroxide (Whiteness Perfect/FGM) on the Vickers microhardness and flexural strength of the restorative composites Filtek Z100 (hybrid), Filtek Z350 (nanofill), Brilliant (micro-hybrid) and Opallis (micro-hybrid). Discshaped (4x2 mm; n=5) and bar-shaped (12x2x1 mm; n=10) specimens of each restorative material were randomly divided into 2 groups: (G1) 16 weeks stored in distilled water; (G2) 16 weeks stored in distilled water, with 16% carbamide peroxide applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 16 publications
2
25
1
1
Order By: Relevance
“…The results of composite microhardness are consistent with results of Hatanaka's study, who suggested the highest hardness is for Z100, followed by Z350 a (34). The difference between composite groups can also be justified based on the amount of their filler.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The results of composite microhardness are consistent with results of Hatanaka's study, who suggested the highest hardness is for Z100, followed by Z350 a (34). The difference between composite groups can also be justified based on the amount of their filler.…”
supporting
confidence: 88%
“…The greatest hardness of composites is related to Z350, followed by Z250, Z100 and P90, respectively. Of course, the type and distribution of composite fillers and the degree of matrix polymerization can also be effective (34).…”
mentioning
confidence: 99%
“…Notwithstanding the relative safety of the treatment, the fact that HP or CP is kept in close contact with the teeth and any associated restorations raises the question of whether the bleaching agent causes undesirable and adverse alterations to the teeth and restorative materials, such as softening and degradation . For this reason, numerous investigations have been conducted to evaluate the effects of bleaching on the properties of restorative materials, such as surface microhardness, surface roughness, color, and flexural strength …”
Section: Introductionmentioning
confidence: 99%
“…Microhardness has drawn much attention in the literature because it is an important physical characteristic of dental materials. 15-18 Hardness of a material has been defined as its resistance against permanent surface indentation or penetration; it depends on a material’s strength, ductility, elastic stiffness, plasticity, strain, toughness, viscoelasticity and viscosity. A material’s ability to abrade or its susceptibility to abrasion by opposing teeth, materials, or being softened by chemical agents has a role in the clinical durability of dental restorations.…”
Section: Discussionmentioning
confidence: 99%